Editorial: About Liminal (state of in-betweenness) - Neves, Pedro Soares (Street Art & Urban Creativity, 2022)
Liminality is the quality of ambiguity or disorientation that occurs in the middle stage of a rite of passage, when participants no longer hold their pre-ritual status but have not yet begun the transition to the status they will hold when the rite is complete. Arnold van Gennep’s in “Les Rites de Passage” (1908), introduced the term into the field of anthropology. Van Gennep drew the attention to liminality, as a new abbreviated form of an individual´s deliberate and voluntary transition into a disoriented, intermediate state – through time amidst a ritual. Since CIAM (Congrès Internationaux d’Architecture Moderne) in 1959 Van Eyck was anthropologizing architecture into in- betweenness. Van Eyck thusly marked the beginning of ‘architectural structuralism’ and stated an attempt to reunite spatial and temporal polarities, to evoke a sense of place. Since the 1950´s, Victor Turner, a cultural anthropologist, on the other hand, reintroduced liminality into anthropology in his essay, “Liminal to Liminoid, in Play, Flow, and Ritual” (1974)